2016
DOI: 10.1122/1.4963800
|View full text |Cite
|
Sign up to set email alerts
|

Steady shearing flow of a moderately entangled polyethylene liquid

Abstract: The rheological properties and dynamical responses of a monodisperse polyethylene (PE) liquid, C 700 H 1402 , were examined using equilibrium molecular dynamics and nonequilibrium molecular dynamics simulations of the atomistically detailed molecules. Equilibrium structural and dynamical properties of the PE liquid, such as the disengagement time (s d ), Rouse time (s R ), entanglement time, (s e ), reptation tube diameter, number of entanglements, and the distribution of the chain end-to-end vector, each foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(128 citation statements)
references
References 44 publications
16
112
0
Order By: Relevance
“…A detailed description of the NEMD simulation methodology used in this study can be found in preceding work, including the SKS potential parameters employed as the united-atom potential model of PE [50,65,66] (also see the Supplemental Material of Ref. [49] for a complete description).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the NEMD simulation methodology used in this study can be found in preceding work, including the SKS potential parameters employed as the united-atom potential model of PE [50,65,66] (also see the Supplemental Material of Ref. [49] for a complete description).…”
Section: Methodsmentioning
confidence: 99%
“…14,23 The underlying reason for the appearance of this damping behavior was demonstrated to be caused by the shear-induced rotational motion of chains, 23,28 further supported by non-equilibrium atomistic simulations. [29][30][31] For this reason, similar undershoots are not expected to occur in elongational flows that are free from rotational contributions to the velocity gradient tensor. 24 We are going to calculate elongational flow properties using the parameters we employed earlier in a quantitative comparison with shear rheological data.…”
Section: Introductionmentioning
confidence: 98%
“…Unentangled C50 and slightly entangled C178 chains have been simulated in bulk and in confined systems. MD has been used to explore the structural, conformational, rheo‐optical, and topological properties of an entangled C400 chains in the linear and highly nonlinear regimes; the dynamics and rheology of supercooled melts of C10 C20 and C150, and C1000 chains; the steady and transient behavior of a C100 melt; the steady and transient behavior of a C400 melt; and steady and startup shear of a C700 melt …”
Section: Introductionmentioning
confidence: 99%
“…MD has been used to explore the structural, conformational, rheo-optical, and topological properties of an entangled C400 chains in the linear and highly nonlinear regimes 30,31 ; the dynamics and rheology of supercooled melts of C10 32 C20 and C150, 33 and C1000 28 chains; the steady 34 and transient 34 behavior of a C100 melt; the steady and transient 31,35 behavior of a C400 melt; and steady and startup shear of a C700 melt. 36,37 In polymer fluids, long-chain entanglement leads to the slow dynamics that makes polymer processing phenomena rich and difficult to predict empirically. These slow dynamics mean that MD of long polymers is extremely difficult without cutting-edge hardware and code.…”
mentioning
confidence: 99%